Brain activity during bladder filling and pelvic floor muscle contractions: A study using functional magnetic resonance imaging and synchronous urodynamics. (1st July 2013) - Krhut, Jan; Holy, Petr; Tintera, Jaroslav; Zachoval, Roman; Zvara, Peter
<x xml:space="preserve">Abstract</x> Objectives To map the brain activity during bladder filling by functional magnetic resonance imaging using a refined scanning protocol including synchronous urodynamics and pelvic floor muscle contractions. Methods A total of 23 healthy female volunteers (age 20–68 years) were enrolled. Participants were asked to contract their pelvic floor muscles. This was followed by a urodynamic examination consisting of repeated filling cycles. Brain activity was measured by functional magnetic resonance imaging using a 3T magnetic resonance system. Measurements of brain activity consisted of 120 functional scans during pelvic floor contractions and 210 scans during bladder filling. Each functional magnetic resonance imaging scan covered the brain with 35 slices. Statistical analyses used the general linear model and independent component analysis. Areas of activation were visualized using group statistics. Results The following main clusters of activation were observed during pelvic floor muscle contractions: medial surface of the frontal lobe (primary motor area), bilaterally; supplementary motor area, bilaterally; and left gyrus precentralis. During bladder filling, activation was detected in the inferior frontal lobe bordering the frontal cingulum, left gyrus parietalis superior, left central area, right insula, brainstem and thalamus with subcortical gray matter nuclei. Conclusions Our work extends an existing functional magnetic resonance imaging protocol for researching the neural control of the lower urinary tract. The present results are consistent with the available literature and agree with the present hypothetical functional model of lower urinary tract neural control.